2017
DOI: 10.1177/1526924817746686
|View full text |Cite
|
Sign up to set email alerts
|

Value of HCC-MELD Score in Patients With Hepatocellular Carcinoma Undergoing Liver Transplantation

Abstract: Our study showed the validity of the HCC-MELD equation in the evaluation of patients undergoing LT for HCC. This score offers a reliable method to assess the risk of waiting list dropout and predict posttransplantation outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 38 publications
1
10
0
Order By: Relevance
“…Also, as expected, age and functional status were major factors associated with survival. In addition, and consistent with the prior literature, 1,2,23,24 we found that persons who underwent transplant in more recent years, all else being equal, had better survival, and those with diabetes, ascites, and hepatic encephalopathy had worse survival.…”
Section: Discussionsupporting
confidence: 90%
“…Also, as expected, age and functional status were major factors associated with survival. In addition, and consistent with the prior literature, 1,2,23,24 we found that persons who underwent transplant in more recent years, all else being equal, had better survival, and those with diabetes, ascites, and hepatic encephalopathy had worse survival.…”
Section: Discussionsupporting
confidence: 90%
“…Generally, TAE is reserved for non-surgical candidates with liver-dominant disease. Patient selection for all locoregional therapies including TAE involves clinical and serologic evaluation of the patient including functional status, liver function tests, and clinical indices such as the ALBI (Albumin-Bilirubin), CP (Child-Pugh), MELD (Model for End-stage Liver Disease), and ECOG (Eastern Cooperative Oncology Group) performance status scores for patient stratification and assessment [34][35][36]. In addition to its role in the diagnosis of HCC, preprocedural imaging is paramount for evaluation of the vascular anatomy, access site patency, and ensuring patency of the portal vein [37].…”
Section: Patient Selectionmentioning
confidence: 99%
“…In addition, the inability to discriminate liver function and clinical outcomes among patients with HCC and well-preserved liver function is a major drawback of the CTP class system, as the majority of patients with HCC are of CTP class A [8, 9]. The MELD score is reliable for stratification of the risk of dropout in patients with HCC [10]. However, this score has limitations when applied to patients with less-severe HCC, and has been evaluated only with those awaiting liver transplantation (LT) with “exception” points [4, 9, 11].…”
Section: Introductionmentioning
confidence: 99%